Russia and Its Neighbors: A Geopolitical Analysis of the Ukrainian Conflict - Michele Pigliucci (Journal of Global Initiatives, 2018)
Within the context of a new Cold War between the Western powers and Russia, one of the most dangerous hot spots is Ukraine. Since 2014, in fact, the Ukrainian army has been engaged in a civil war against Russian-backed troops of self-proclaimed Donetsk and Luhansk Republics. This crisis appears as a new geopolitical tool both for Russia and for the United States: for the former, in order to contain NATO expansion, for the latter, in order to counteract Russian influence and to open the way for U.S. liquefied natural gas exports in Europe, reducing European energy dependence on Russia (Chornii, 2015; Marples, 2016). The Ukrainian position is strategic: it is one of the main transit routes of Russian natural gas to European countries, with three main pipeline corridors. Knowledge of Ukraine’s geographic situation is needed in order to better understand the evolving crisis in the region.